2019
DOI: 10.1177/0145561319881856
|View full text |Cite
|
Sign up to set email alerts
|

The Result of Treatment of Deep Neck Infection in Patients Referred According to Public Health System

Abstract: There are many factors that result in the treatment of deep neck infection (DNI). This study aims to compare the results of DNI treatment between referred and walk-in patients. This retrospective cohort study reviewed the data of 282 DNI patients. The peritonsillar abscesses and limited intraoral abscesses were excluded. The outcome of treatment such as duration of hospital stay, the expense of treatment, morbidity, and mortality were reviewed during staying in the hospital. A total of 282 patients were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Similarly to the findings of Kauffmann and Cordesmeyer, a significant proportion of patients displayed hyperglycemia at admission and in these cases the hospitalization time has been significantly longer [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 65%
“…Similarly to the findings of Kauffmann and Cordesmeyer, a significant proportion of patients displayed hyperglycemia at admission and in these cases the hospitalization time has been significantly longer [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 65%
“…Of the systemic diseases contributing to mortality, several previous reports addressed death due to complications with sepsis (25,(30)(31)(32)(33). In contrast to the outcome related to DNM, the present study showed that sepsis was a signi cant factor only for mortality, with an adjusted OR of 3.32 (95%CI 2.29-4.82), not for a delay in oral dietary intake, with an adjusted OR of 1.15 (95%CI 0.88-1.51).…”
Section: Discussionmentioning
confidence: 99%
“…1 Among all the deep neck spaces, masticator space is the most prevalent site of spread of odontogenic infection. 2 Deep neck infection (DNI) is a prevalent bacterial infectious disease found in all age groups 3 and a common emergency condition in otorhinolaryngology. 4 Deep neck infection can extend into the airway and mediastinum and potentially be life-threatening, particularly in patients with systemic diseases 5-7 and elderly individuals.…”
Section: Discussionmentioning
confidence: 99%